(untitled) (Kronika Bydgoska, 2020)
During the 1870s, the Prussian educational legislation from the period of Kul- turkampf issued a number of regulations restricting and affecting teaching of the Polish language. Resolutions issued afterwards led to the complete removal of this subject from schools. Progressing Germanization of the education system led to various forms of repression against Polish students, which resulted in a wave of school strikes and social protests. One of the methods of defense of the Polish language, culture and tradition was organizing clandestine teaching and self-learning groups. This article presented the patriotic role of Polish women, who in Bydgoszcz, in the period of the Prussian Partition, fulfilled the role of guardians of culture by offering clandestine classes in the Polish language, literature and history. The article also presented activity of Polish institutions as well as social, cultural and educational associations, supporting the fight for Polish education and national identity. It also described in brief initiatives aimed at Polonization of the education system in Bydgoszcz, undertaken since 1918.